Combined Face–Brain Morphology and Associated Neurocognitive Correlates in Fetal Alcohol Spectrum Disorders. (20th July 2018) - Suttie, Michael; Wozniak, Jeffrey R.; Parnell, Scott E.; Wetherill, Leah; Mattson, Sarah N.; Sowell, Elizabeth R.; Kan, Eric; Riley, Edward P.; Jones, Kenneth L.; Coles, Claire; Foroud, Tatiana; Hammond, Peter; et al.
Abstract : Background: Since the 1970s, a range of facial, neurostructural, and neurocognitive adverse effects have been shown to be associated with prenatal alcohol exposure. Typically, these effects are studied individually and not in combination. Our objective is to improve the understanding of the teratogenic effects of prenatal alcohol exposure by simultaneously considering face–brain morphology and neurocognitive measures. Methods: Participants were categorized as control ( n  = 47), fetal alcohol syndrome (FAS, n  = 22), or heavily exposed (HE) prenatally, but not eligible for a FAS diagnosis (HE, n  = 50). Structural brain MRI images and high‐resolution 3D facial images were analyzed using dense surface models of features of the face and surface shape of the corpus callosum (CC) and caudate nucleus (CN). Asymmetry of the CN was evaluated for correlations with neurocognitive measures. Results: (i) Facial growth delineations for FAS, HE, and controls are replicated for the CN and the CC. (ii) Concordance of clinical diagnosis and face‐based control–FAS discrimination improves when the latter is combined with specific brain regions. In particular, midline facial regions discriminate better when combined with a midsagittal profile of the CC. (iii) A subset of HE individuals was identified with FAS‐like CN dysmorphism. The average of this HE subset was FAS‐like in its facial dysmorphism. (iv) Right–left asymmetry found in the CNs of controls is not apparent for FAS, is diminished for HE, and correlates with neurocognitive measures in the combined FAS and HE population. Conclusions: Shape analysis which combines facial regions with the CN, and with the CC, better identify those with FAS. CN asymmetry was reduced for FAS compared to controls and is strongly associated with general cognitive ability, verbal learning, and recall in those with prenatal alcohol exposure. This study further extends the brain–behavior relationships known to be vulnerable to alcohol teratogenesis. Abstract : The structural development of the face and brain is intrinsically linked by a multitude of factors. In‐utero alcohol exposure at key time points in gestation has a detrimental impact on these factors, causing a range of structural abnormalities. This analysis shows how the relationships between face, brain and cognition can be utilised to better identify those with fetal alcohol spectrum disorders.